Regulation of the angiopoietin-Tie ligand-receptor system with a novel splice variant of Tie1 reduces the severity of murine arthritis. - Malik, N; Jin, P; Raatz, Y; Sumariwalla, P; Kiriakidis, S; Shepard, M; Feldmann, M; Paleolog, E (2010)
OBJECTIVES: To determine the function of the angiopoietin (Ang)-Tie ligand-receptor system, and to assess the effect of Tie1-751, a naturally occurring extracellular domain of the Tie1 receptor derived by alternative splicing, in an in vivo model of RA. METHODS: In the murine CIA model, expression of endogenous Ang1, Ang2, Tie1 and Tie2 in whole paws was analysed by quantitative RT-PCR. To assess the effect of inhibition of the Ang-Tie axis, Tie1-751 was expressed and fused to the Fc fragment of human IgG1. The effect of Tie1-751-Fc on human umbilical vein endothelial cell (HUVEC) cytoprotection and migration in response to Ang1, either alone or in combination with VEGF, was investigated. Furthermore, an in vitro angiogenesis assay was used to determine the effect of Tie1-751-Fc on Ang1-mediated angiogenesis. Finally, Tie1-751-Fc was administered in CIA, and the effects on clinical disease and joint architecture of hind foot specimens were determined. RESULTS: Gene expression levels of Ang1, Ang2, and receptors Tie1 and Tie2 in whole paws were significantly increased during the progression of arthritis. Tie1-751-Fc significantly inhibited HUVEC cytoprotection and migration in response to Ang1 alone, or Ang1 in combination with VEGF. Tie1-751-Fc also significantly inhibited angiogenesis induced by a combination of Ang1 plus VEGF. Finally, Tie1-751-Fc, when administered intra-peritoneally to arthritic mice, reduced clinical signs of arthritis, damage to joint architecture and infiltration of blood vessels into the synovium. CONCLUSIONS: Our data demonstrate that the Ang-Tie ligand-receptor system is dysregulated in CIA. Tie1-751, a novel splice variant of the Tie1 receptor, inhibits Ang1/VEGF signalling, suggesting that Ang inhibition may be of therapeutic benefit in inflammatory arthritis.